Psychological Well-Being of Junior High School Students : Preliminary Study for Developing a Mental Health-Based School Counseling Model in Wetland Environments - Sulistiyana Sulistiyana; Muhammad Arsyad; Noor Ainah (Bulletin of Counseling and Psychotherapy, 2026)
Psychological well-being is an important indicator of adolescent development, particularly among junior secondary school students living in riverbank areas with distinctive social and ecological challenges in wetland environments. This study used a descriptive qualitative survey design to describe the psychological well-being of junior high school students residing in riverbank communities in Banjarmasin City. The participants were 184 students from three junior high schools located along the riverbanks. Data were collected using a psychological well-being questionnaire based on Ryff’s theoretical framework, covering six dimensions: autonomy, environmental mastery, personal growth, positive relations with others, purpose in life, and self-acceptance. The data were analyzed descriptively to identify general patterns and the dominant dimensions of students’ psychological well-being. The results showed that most students (83.2%) had a moderate level of psychological well-being, while 15.2% were in the high category, and 1.6% were in the low category. The main weaknesses were observed in autonomy (52.7% low) and environmental mastery (56.0% low). In contrast, strengths appeared in personal growth (36.4% high) and purpose in life, with more than 60% of students falling within the moderate to high range. These findings indicate that although students have motivation and a sense of direction in life, they still face challenges related to independence and the management of their social and academic environments. The study highlights the need for school guidance and counseling services to implement a context-sensitive multitiered system of support (MTSS) that aligns with the ecological and cultural characteristics of riverbank communities in wetland environments.